Prevalencia de Blastocystis sp en niños en edad escolar de Reynosa, México - Ramsés Orlando Lara-Medina (Infectio, 2021)
Objective: To determine the prevalence of Blastocystis spp. in children living in the city of Reynosa, Tamaulipas, Mexico.Material y Method: Cross-sectional study that included 238 stool samples from children aged 5 to 12 years from elementary schools in the city of Reynosa,Tamaulipas, Mexico.Results: Of the total number of samples, 13.8% showed the presence of Blastocystis spp., being the most prevalent among the parasites found; the presence of Entamoeba histolytica/dispar, Giardia intestinalis and Enterobius vermicularis was also reported.Conclusions: The prevalence of Blastocystis in areas of Mexico is poorly known; however, studies in various parts of the world suggest an increase, so it is importantto determine the presence and its relationship as a human pathogen or opportunist.